Developing a strategic approach to facilitate sustainable facilities management (SFM) practice for universities in developing countries / Mohamad Sufian Hasim - Hasim, Mohamad Sufian (College of Built Environment, 2023)
Sustainability practices in facilities management (FM) are vital in reducing the impact of buildings on the natural environment.